Analysis of the Clinicopathologic Characteristics of Lung Adenocarcinoma With CTNNB1 Mutation - Zhou, Chao; Li, Wentao; Shao, Jinchen; Zhao, Jikai; Chen, Chang (Frontiers in Genetics, 2020)
Introduction: Lung adenocarcinoma with CTNNB1 mutation is relatively uncommon, and its clinicopathologic characteristics, disease course, and prognosis have not been well-studied. Methods: A total of 564 lung adenocarcinoma patients were enrolled in this study. The relationship between CTTNB1 mutational status and clinicopathologic parameters, the rates of relapse-free survival (RFS) and overall survival (OS), and the mutational status of other genes commonly mutated in lung adenocarcinoma were analyzed. Results: Of 564 lung adenocarcinoma patients, 30 (5.3%) harbored CTNNB1 mutations. Univariate analyses revealed that gender, smoking history, pleural invasion, and histological subtype were all significant predictors of RFS and OS. Pleural invasion and histological subtype remained significant predictors of RFS and OS in a multivariate analysis. There were no significant differences in RFS (p=0.504) or OS (p=0.054) between lung adenocarcinoma patients with CTNNB1 mutation and those without CTNNB1 mutation. However, patients with CTNNB1 mutation tended to have a worse OS. Conclusions: Female patients and non-smokers are likely to harbor CTNNB1 mutation and Primary lung adenocarcinoma with mutated CTNNB1 has a poor prognosis.